Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak UMKM di Kecamatan Balikpapan Kota - Fice Handayani; Bachtiar Bachtiar; Nur Khomariah (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The purpose of this research is to examine the factors that can affect UMKM taxpayer compliance, especially in Balikpapan Kota Subdistrict, namely knowledge and understanding of Government Regulation on taxation (PP No.46, 2013), taxpayer awareness, tax authorities services and modernization of the tax administration system. The sample used was 58 UMKM respondents who were registered in the Office of Cooperative, MSMEs, and industry in the city of Balikpapan. The sampling method uses the formula of Isaac and Michael with an error rate of 5%. In need of validity and reliability test for research instruments and multiple linear regression to analyze data. From the results obtained by the awareness of taxpayer and modernization of the tax administration system has a significant influence on the taxpayer compliance of UMKM Balikpapan City District. And other factors, namely the understanding of Government Regulations concerning taxation and tax authorities services do not have a significant effect. And the dominant influence is the modernization of tax administration systems such as e-filing, e-SPT, and others